An Effective Analysis on Burnout and Anger among Police Personnel: Exploring the Impact of Chronic Burnout and Anger on Police Personnel (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Burnout is viewed as a chronic negative psychological process that occurs among workers in the occupations requiring substantial interpersonal contact (Leiter 1993). Associated difficulties include cognitive characteristics (e.g. emotional exhaustion, irritability) behaviour characteristics (absenteeism and declining work performance), and somatic complaints. It is a syndrome of emotional exhaustion, depersonalization and diminished personal accomplishment. It was originally proposed to reflect a state of physical and emotional depletion amongst human service employees that resulted from the conditions of the work environment.